Research on resource allocation algorithm of wireless network based on game feedback. Issue 2 (3rd July 2021) - Liu, Juefu
In order to solve the problems of poor de-noising low-resource utilisation, low fairness and serious interruption in resource allocation algorithm of wireless network based on chaotic immune algorithm, a wireless network resource allocation algorithm based on game feedback is proposed in this paper, which combines wavelet transform domain interpolation with low-pass filter combination. Effective de-noising of transmission resources; classification of users based on game theory, establishment of optimisation utility function, analysis of channel distribution. By comparing the two existing algorithms, the simulation environment is constructed, and the performance comparison experiments are carried out from four aspects: de-noising effect, resource utilisation, fairness and interruption. The results show that the algorithm is highly de-noising, improve the efficiency of resource utilisation and fairness of allocation, and allocates 0 interruption rate. Therefore, the method can flexibly configure and dynamically adjust the available resources of wireless transmission part to maximise transmission efficiency.